Komunikasi Interaktif dalam Mengurangi Kecemasan Keluarga Penderita COVID-19 di Ruang ICU - Lono Wijayanti; Yurike Septianingrum; Sulistyorini Sulistyorini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: Anxiety is the most common feeling experienced by families when there are health problems in their family members. Communication that is built between nurses and family members if it doesn't go well, will cause anxiety for family members of COVID-19 patients who are treated in the intensive room (ICU). Objective: The purpose of this study was to analyze the relationship between nurse communication and anxiety in the ICU room of RSI A. Yani. Methods: This study is a correlational analytic study. The population in this study were all families of patients who underwent Covid-19 isolation in the ICU room of the Islamic Hospital A. Yani Surabaya as many as 70 respondents, a sample of 60 respondents, using Probability Sampling sampling technique simple random sampling. The independent variable in this study was interactive communication, while the dependent variable was anxiety. The data were analyzed using the spearman rank statistical test. Results: The results showed that from 60 respondents, most (63.3%) nurses were sufficient in interactive communication and most (70%) of the patient's family did not experience anxiety. Based on the spearman rank test, p value = 0.000 (p <0.05), there is a relationship between nurse communication and anxiety levels in family members with COVID-19 in the ICU. Conclusion: The better the communication applied by nurses to the patient's family, the less anxiety experienced by the patient's family, it is hoped that nurses can improve interactive communication techniques, especially in dealing with patients undergoing Covid-19 isolation.